Philippines: Father–daughter succession in family business: A Philippine case study - Santiago, Andrea L. (Animo Repository, 2016)
This chapter presents the case study on father daughter succession in a Russian family business. The case study offers some insight into the main phases of a succession process pertinent to the business environment and cultural values of Russia, as well as the factors which are relevant for succession planning and management. It helps managers of family businesses understand how to plan and successfully manage the succession process in order to survive generational change accompanied by the management of gender change. The free market economy is still developing in Russia. Family businesses share common characteristics and face common problems, among which generational change is recognized to be the most relevant. Russian pre-revolutionary history brings multiple examples of successful family businesses; however, the segment is currently in its embryonic state. Adapting Russian legislation to the standards of international law became extremely urgent in 1990s as a result of the fundamental changes taking place in the country's social and political order. © 2011 Daphne Halkias, Paul W. Thurman, Celina Smith, Robert S. Nason and the contributors.